Lateral or medial approach for valgus knee in total knee arthroplasty - which one is better? A systematic review - Wang, Bin (J Int Med Res, 2019)
OBJECTIVE: To identify whether the medial or lateral approach is superior for patients with valgus knees undergoing primary total knee arthroplasty (TKA). METHODS: Studies evaluating the 2 approaches were sourced from the PUBMED, EMBASE, Web of Science, and OVID databases. The quality of included studies was assessed using a modified quality evaluation method, and differences between approaches were systematically reviewed. RESULTS: Seventeen observational studies were included. The studies were published between 1991 and 2016, and included 5 retrospective studies and 12 prospective studies. Sixteen evaluation methods for the study outcomes were identified. Twelve and eight complication types were identified by studies reporting the lateral and medial approaches for valgus knee, respectively. Several studies showed that pain scores and knee function were superior using a lateral approach. CONCLUSION: The lateral approach (combined with a tibial tubercle osteotomy or proximal quadriceps snip) was more useful and safer than the medial approach in the treatment of severe uncorrectable valgus knee deformity in patients undergoing TKA. Most of the available evidence supports the use of a lateral approach provided that the surgeon is familiar with the pathological anatomy of the valgus knee.